Feasibility and acceptability of self-directed, remote dim-light melatonin onset collection in pediatric patients diagnosed with chronic pain - Tacugue, Nicole; Love, Jessica J.; Cherry, Jakob M.; Lane, Jacqueline; Kossowsky, Joe (Frontiers in Sleep, 2025)
IntroductionSleep dysregulation is highly prevalent in pediatric chronic pain conditions and associated with poorer clinical outcomes. Interactions between underlying circadian misalignments and pain in pediatric populations remain unclear. Dim-light melatonin onset collections conducted in external lab settings are standard for measuring circadian rhythmicity by examining fluctuations in melatonin levels. However, present limitations prevent us from capturing a typical night's sleep and minimize accessibility to broader populations due to geographic, financial, and temporal barriers. We investigated a novel approach in which participants complete collections in an entirely self-directed manner using an at-home diagnostic kit.MethodsParticipants included pediatric patients with diagnosed chronic pain and healthy controls. The 3-week protocol involved sleep, activity, and light tracking, self-reported sleep diaries, a survey determining morningness-eveningness chronotypes, one self-directed home dim-light melatonin onset collection with objective compliance measures, and assessment of study protocol acceptability.Results and discussionIn a sample of pediatric patients with diagnosed chronic pain (N = 6, Mage=14.5, SD = 2.74, 66.7% female) and a subset of healthy controls (N = 6, Mage =13.3, SD=2.73, 50% female), both the Hockeystick method and 3 pg/ml dim-light melatonin onset threshold were employed to calculate salivary dim-light melatonin onset times in 8 of the 12 participants. On average, dim-light melatonin onset times were 1 h and 43 min earlier than self-reported sleep onset times. Our results illustrate the feasibility and accuracy of self-directed, remote dim-light melatonin onset collections in pediatric populations. With supplementary research validating this optimized approach to measure endogenous circadian phase, more specific aspects of sleep can be targeted in pain intervention strategies to further optimize clinical outcomes in a greater population of pediatric patients.